Essentials of Hamiltonian dynamics - Lowenstein, John H. (Cambridge University Press, 2012)
"Classical dynamics is one of the cornerstones of advanced education in physics and applied mathematics, with applications across engineering, chemistry, and biology. In this book, the author uses a concise and pedagogical style to cover all the topics necessary for a graduate-level course in dynamics based on Hamiltonian methods. Readers are introduced to the impressive advances in the field during the second half of the twentieth-century, including KAM theory and deterministic chaos. Essential to these developments are some exciting ideas from modern mathematics, which are introduced carefully and selectively. Core concepts and techniques are discussed, together with numerous concrete examples to illustrate key principles"--